Muslim women in America the challenge of Islamic identity today - Haddad, Yvonne Yazbeck 1935-; Smith, Jane I.; Moore, Kathleen M., d 1959- (Oxford University Press, 2006)
Muslim women living in America continue to be marginalized and misunderstood since the 9/11 terrorist attacks, yet their contributions are changing the face of Islam as it is seen both within Muslim communities in the West and by non-Muslims